Building better adapters: optimising the career construction model of adaptation - Sam, Yoke Loo (2024)
Career adaptability, defined as the competency to navigate unfamiliar, complex problems in vocational tasks, has emerged as a crucial asset for managing career transitions. This study investigated the underlying structure of Savickas and Porfeli's Career Construction Model of Adaptation (CCMA) in a sample of young to mid-career working adults in Singapore. To address variations in how existing research has operationalised the CCMA's four dimensions (adaptivity, adaptability, adapting, and adaptation; “4As”), we employed psychometric techniques on 16 established self-reported assessments to examine the shared variances among these assessments representing the “4As”. Factor analysis identified a parsimonious model with four common factors aligning with the conceptualisation of the “4As”. Subsequently, path analysis with bootstrapping confirmed significant positive relationships between all four factors, suggesting a serial mediation process where "adaptivity" directly influences "adaptation" and indirectly influences it through the mediating factors "adaptability" and "adapting". Our findings provide a clearer understanding of the interrelationships within the CCMA, potentially informing future research by offering a streamlined structure for assessing career construction processes.